Determination of an optimum sampling rate for the collection of solar radiation data - Davis, John Moulton, 1938-, author; Cox, Stephen K., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1982)
An analysis of total sky and direct component shortwave solar radiation data.
September, 1982.
Keywords: Radiation -- Measurement; Solar radiation